Integrated analysis of transcriptome, sRNAome, and degradome involved in the drought-response of maize Zhengdan958 - Yang Shuqiong; Liu Jiafei; Cao Lingling; Chen Jibao; Duan Pengfei (Open Life Sciences)
Drought is a major abiotic stress in restricting the growth, development, and yield of maize. As a significant epigenetic regulator, small RNA also functions in connecting the transcriptional and post-transcriptional regulatory network. Further to help comprehending the molecular mechanisms underlying drought adaptability and tolerance of maize, an integrated multi-omics analysis of transcriptome, sRNAome, and degradome was performed on the seedling roots of an elite hybrid Zhengdan958 under drought stress. In this study, 2,911 genes, 32 conserved miRNAs, and 12 novel miRNAs showed a significantly differential expression under drought stress. Moreover, 6,340 target genes of 445 miRNAs were validated using degradome sequencing, forming 281 miRNA–mRNA pairs in control (CK) and drought-stressed (DS) library. These target genes were mainly involved in the plant hormone signal transduction and phenylpropanoid biosynthesis pathways. The integrated multi-omics analysis revealed that five DEmiRNA–mRNA pairs displayed negatively correlated expression patterns, which were also verified by qRT-PCR. Tissue-specific expression profile and regulatory network analysis revealed that miR528a/b-Zm00001d021850, miR408a/b-Zm00001d020794, and miR164e-Zm00001d003414 might be essential in root-specific drought stress response of maize Zhengdan958 seedlings. These worthwhile will promote the functional characterization of miRNA–mRNA modules response to drought stress, and potentially contribute to drought-resistance breeding of maize.